Smart Technology in Construction Industry: Opportunity during COVID-19 Pandemic - Putri Fatimah; Ahyahudin Sodri; Udi Syahnoedi Hamzah (Universitas Sanata Dharma, 2023)
The construction industry is a sector that plays an essential role in economic growth. The COVID-19 pandemic is an uncertain situation that significantly affects humans and industries, including the construction industry. The operational construction projects are complex with various activities and involve a large of workers. Prevention of the spread of COVID-19 that changes lifestyles and improves technology adoption. This study examines the relationship between increased technology adoption and limited workers’ social interaction in construction projects during the pandemic. A questionnaire survey was conducted to construction workers in DKI Jakarta, 74 valid responses were collected and correlation analyses were performed with SPSS version 28. The result of this study indicated a significant and positive correlation between increased technology adoption and limited workers’ social interaction in a construction project during the pandemic. There are opportunities for the construction industry to implement a digital transformation, Building Information Modelling (BIM), and intelligence visualization technologies to cope with the impact of the COVID-19 pandemic on construction activities. This study provides evidence that smart technologies application has a significant role in supporting the construction industry to mitigate the impact of the COVID-19 pandemic and opportunities for continuous improvement towards post-pandemic.